High-Grade Neuroendocrine Carcinoma with Bronchial Intraepithelial Tumor Spread. Issue 9 (September 2015) - Kojima, Hideaki; Watanabe, Reiko; Isaka, Mitsuhiro; Shimizu, Reiko; Kayata, Hiroyuki; Miyata, Naoko; Maniwa, Tomohiro; Takahashi, Shoji; Ito, Ichiro; Kameya, Toru; Funai, Kazuhito; Ohde, Yasuhisa; et al.
<x xml:space="preserve">Abstract</x> Introduction: During surgical resection of a peripherally located high-grade neuroendocrine carcinoma (HGNEC), we unexpectedly discovered prominent bronchial intraepithelial tumor spread up to the surgical end of the bronchus. Because bronchial intraepithelial tumor spread of peripherally located HGNEC has been rarely reported, we conducted a retrospective analysis at our hospital. Methods: We histologically reviewed surgically resected HGNEC cases to assess bronchial intraepithelial spread of tumor cells. HGNECs with bronchial intraepithelial tumor spread were further studied by immunohistochemistry for neuroendocrine markers, and their clinicopathological characteristics were evaluated. Results: Of 1778 cases of surgically resected lung cancer in our hospital, 47 cases of HGNEC were evaluated. Bronchial intraepithelial tumor spread was observed in nine cases (19.1%); eight of these cases were large-cell neuroendocrine carcinoma (LCNEC) or small-cell lung carcinoma with an LCNEC component. Moreover, bronchial intraepithelial tumor spread was continuous from the primary tumor to the resected end of the bronchus in four cases, and all these cases had an LCNEC component. Furthermore, HGNEC with bronchial intraepithelial tumor spread was associated with a higher recurrence rate than no bronchial intraepithelial tumor spread. Conclusion: The results of this study suggest that bronchial intraepithelial tumor spread is commonly observed in cases of peripherally located HGNEC and may be a unique form of tumor invasion, especially tumors with LCNEC morphology. Therefore, surgeons and pathologists should be cognizant of bronchial intraepithelial tumor spread in peripherally located HGNEC, as well as its potential role as an indicator of HGNEC aggressiveness.